SONOGRAPHIC DETERMINATION OF FETAL AGE IN SANGAMNERI AND OSMANABADI GOATS - AMLE, M B; BAKSHI, S A; BIRADE, H S; GULAWANE, S U; BANNALIKAR, A S (The Indian Journal of Animal Reproduction, 2023)
Fetometry by real-time ultrasonography proved to be reliable method for predicting gestational age inSangamneri and Osmanabadi goats utilizing biometric parameters viz. Bi Parietal Diameter (BPD) of fetus andPlacentome Diameter (PL).
Keywords: Fetal age; Bi Parietal Diameter; Placentome Diameter; Sangamneri; Osmanabadi; Goats